Fostering Religious Moderation in Children: Parental Approaches in the Era of Industry 4.0 - Mufatihatut Taubah; Dewi Ulya Mailasari; Nor Faiz; Farida Isroani (Jurnal Teknologi Pendidikan)
Religious moderation is crucial for fostering harmony in diverse societies but faces challenges such as extremism, social polarization, and discrimination against minorities. In Indonesia, efforts to strengthen religious moderation include interfaith dialogue and community programs. Early childhood education plays a vital role in instilling moderate values, helping prevent radicalization, and promoting tolerance. This study explores parental strategies for fostering religious moderation among children in the Industry 4.0 era. Using a case study approach, data were collected from six families in rural Madura. Findings indicate that religious education, parental role modeling, and community participation significantly shape children's moderate attitudes. However, challenges include parental busyness, excessive digital exposure, and permissive parenting. Strengthening religious moderation requires a balanced approach integrating education, guidance, and social engagement to nurture a generation that respects diversity and coexists peacefully in a pluralistic society.